Sexual orientation & human rights in American religious discourse - Olyan, Saul M.; Nussbaum, Martha Craven (Oxford University Press, 1998)
Introduction : contemporary Jewish perspectives on homosexuality / Saul M. Olyan -- Religious communities, secular society, and sexuality : one Jewish opinion / David Novak -- Sexual orientation and human rights : a progressive Jewish perspective / Judith Plaskow -- Constructing a Jewish sexual ethic : a rejoinder to David Novak and Judith Plaskow / Louis E. Newman -- Introduction to Roman Catholic perspectives on sexual orientation, human rights, and public policy / Sumner B. Twiss -- Sexual orientation and human rights : a Roman Catholic view / James P. Hanigan -- Sexual orientation and human rights in American religious discourse : a Roman Catholic perspective / Charles E. Curran -- Response to James Hanigan and Charles Curran / Margaret A. Farley -- Introduction to essays representing mainline Protestant churches / Keith Green -- The prophetic stand of the ecumenical churches on homosexuality / Max L. Stackhouse -- Sanctification, homosexuality, and God's triune life / Eugene F. Rogers, Jr. -- Response to Max Stackhouse and Eugene Rogers / Kathryn Tanner -- Introduction : three perspectives on gays in African-American ecclesiology and religious thought / Lewis R. Gordon -- Sexual orientation and human rights discourse in the African-American churches / Cheryl J. Sanders -- Deadly silence : reflections on homosexuality and human rights / Victor Anderson -- Sexual orientation and the language of higher law / William D. Hart -- Sexual and religious pluralism / Andrew Koppelman -- What would it mean to have a "First Amendment" for sexual orientation? / Michael W. McConnell.